Innovation paradoxes: a review and typology of explanations. (2nd October 2017) - Fragkandreas, Thanos
ABSTRACT: The concept of innovation paradoxes refers to a family of anomalous observations demonstrating that relatively high or outstanding innovation efforts lead to either insignificant or undesirable outcomes. While researchers have long been busy studying the nature and causes of innovation paradoxes, they have yet to assess the fruits of their research efforts. This paper addresses this neglect, in particular by identifying and reviewing the literature of two innovation paradoxes – the European innovation paradox and the Swedish innovation paradox. The findings show that research on both paradoxes has proceeded along similar lines, leading to the development of a working explanatory typology of innovation paradoxes. The paper ends with a discussion of key observations, findings and suggestions.